The East-West-German Productivity Gap: Lessons from firm-level data? - Steffen Müller (Wirtschaftsdienst)
Abstract According to national accounts, the East German economy is at only 80 % of West German labour productivity even 30 years after the fall of the Iron Curtain. This difference in aggregate labour productivity goes hand in hand with many of the economic and societal problems East Germany faces today. To understand the sources of the aggregate productivity gap, this study discusses recent literature on the East-West gap that applies granular firm and product level data. The evidence clearly shows the relevance of firm-level productivity differences for the aggregate gap and challenges common hypotheses derived from aggregate data.